2017
DOI: 10.1002/ejp.1025
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the pain continuum after adolescent idiopathic scoliosis surgery: A prospective cohort study

Abstract: Background Chronic postsurgical pain (CPSP) affects half a million children annually in the United States, with dire socioeconomic consequences, including long-term disability into adulthood. The few studies of CPSP in children are limited by sample size, follow-up duration, non-homogeneity of surgical procedure and factors evaluated. Methods In a prospective study of 144 adolescents undergoing a single major surgery (spine fusion), we evaluated demographic, perioperative, surgical and psychosocial factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
170
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(177 citation statements)
references
References 43 publications
5
170
2
Order By: Relevance
“…It has been previously shown that psychological and clinical variables contribute to CPSP 31. This study finds associations between epigenetics and CPSP in children for the first time and adds to the emerging evidence linking epigenetic mechanisms to the development of chronic pain states 41.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been previously shown that psychological and clinical variables contribute to CPSP 31. This study finds associations between epigenetics and CPSP in children for the first time and adds to the emerging evidence linking epigenetic mechanisms to the development of chronic pain states 41.…”
Section: Discussionsupporting
confidence: 65%
“…Demographics and patients’ clinical characteristics were summarized as mean (standard deviation [SD]), median, and frequency (percentage) according to the distribution of the data. Prior to evaluation of the association between pain outcome and DNA methylation, the effects of covariables were tested, which included age, sex, race, morphine dose in mg/kg on POD 1 and 2, preoperative anxiety score (VAS), preoperative pain score, duration of surgery, vertebral levels fused, propofol and remifentanil doses used during surgery (per kg), use of intravenous acetaminophen/ketorolac (yes/no), diazepam doses (mg/kg), and pain catastrophizing scale (parent version) and parent pain history scores and sequential scores for Childhood Anxiety Sensitivity Index and pain catastrophizing scale (child version) 31. Three pain outcomes were examined.…”
Section: Methodsmentioning
confidence: 99%
“…This discrepancy in findings may be due to the presence and stronger predictive value of the baseline cluster of psychological and somatic symptoms (ie, depression, fatigue, pain worry, neuropathic‐like symptoms). Others have similarly found strong and independent associations between psychological characteristics such as “anxiety sensitivity”, child pain catastrophizing and long‐term postoperative pain outcomes. Our data provide a more comprehensive description of the psychological and somatic characteristics that may cluster together to predict long‐term pain trajectories after surgery.…”
Section: Discussionmentioning
confidence: 91%
“…In this retrospective study of children and adolescents who had undergone extensive abdominal surgery, over a third of the patients reported persistent opioid use up to 6 months after surgery, and approximately one out of every ten children were still taking opioids 2 years after surgery. This rate of persistent opioid use was higher than those reported in the pediatric nononcologic surgical population . For comparison, the reported rates of persistent opioid use in children who have undergone scoliosis surgery range from less than 1% to 11% .…”
Section: Discussionmentioning
confidence: 56%